Insights from Design Processes Used in Developing Exergames - Lund, Alexander Hvidbjerg Kjær; Sørensen, Amalie Finnemannn; Elbæk, Lars; Kaos, Maximus D (European conference on games based learning, 2021)
Participation rates in physical activity are low, and with gyms closing and lockdowns becoming a necessary tool to fight the global pandemic, evidence suggests COVID-19 is only exacerbating the issue. People are becoming more sedentary as they stay at home longer and do more home office work. Exergames-games that require physical exertion to play-hold promise to combat sedentary behaviours, since they are typically inexpensive and can be played at home. Despite their potential to motivate people to move, it is challenging to design exergames because they must strike a balance between exercise and play. Current research in exergames provides some advice and guidelines on best practices for developing movement-based games. But, to date little attention has been given to the design processes that lead to the development of these guidelines. This paper aims to fill this gap by contributing 1) an in-depth discussion of and insights gained from the design process used when developing an exergame and 2) a novel movement-based method used in the development of a virtual reality (VR) exergame-VR bodystorming. We illustrate these methods through the development of Diverging Squash (DS), a novel VR squash game. We reveal insights throughout the entire design process from the beginning stages using brainstorming to focus on players' needs and motivation for physical activity, to using exertion cards for framing the game's primary elements. Exertion cards, for example, aided in our decision to gradually increase the difficulty of the game during play. We further demonstrate how our novel VR bodystorming method, or bodystorming in a virtual environment while wearing a VR headset, can be a useful tool for designers. For instance, during a VR bodystorming session, we practiced holding a virtual paddle in the VR environment in different ways. Insights from the way it was being held in VR led to adjustments to the way the paddle should be gripped, and the force needed to hit the ball. We conclude with key takeaways that give designers a view into how design methods for exergames are applied in practice and, thus, how they can be used in their own work.